2013
DOI: 10.1164/rccm.201304-0691oc
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Ventilation Triggers Hippocampal Apoptosis by Vagal and Dopaminergic Pathways

Abstract: These results prove the existence of a pathogenic mechanism of lung stretch-induced hippocampal apoptosis that could explain the neurological changes in ventilated patients and may help to identify novel therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
104
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(108 citation statements)
references
References 50 publications
1
104
2
Order By: Relevance
“…Expanding preclinical evidence suggests mechanical lung injury may cause brain injury via several complex pathways (17)(18)(19)(20)(21), paralleling clinical trials data that have revealed lungprotective ventilation attenuates other extrapulmonary organ dysfunctions (8,9).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Expanding preclinical evidence suggests mechanical lung injury may cause brain injury via several complex pathways (17)(18)(19)(20)(21), paralleling clinical trials data that have revealed lungprotective ventilation attenuates other extrapulmonary organ dysfunctions (8,9).…”
mentioning
confidence: 86%
“…Insults ranging from acute myocardial infarction (44,45) to sepsis (46,47) have been shown to increase intracerebral proinflammatory cytokine levels and associated neuronal injury. Several studies similarly have implicated lung injury as a precipitant of neuroinflammation and brain injury (17)(18)(19)(20). Even absent preexisting lung injury, recent data suggest lung mechanotransduction during high-VT ventilation may induce vagal afferentmediated apoptotic pathways in the brain (17,18).…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, despite the potential to improve long-term cognitive outcomes by improving oxygenation (33) or reducing lung stretch (35,36) in the case of proning or indirectly by shifting the balance between oxygen delivery and oxygen consumption to a more favorable position in the case of neuromuscular blocking agents (32), the effects of these interventions on long-term outcomes remain speculative.…”
Section: Perspectivesmentioning
confidence: 99%
“…Cognitive impairment, an outcome of vital importance to ARDS survivors and their caregivers (37), is common after ARDS (11,13,15,16). Emerging evidence suggests that mechanical ventilation per se may trigger neuronal apoptosis via vagal and dopaminergic pathways (36). In contrast to mechanical ventilation, which is required to support life in ARDS, the selected oxygenation target range may be a potentially modifiable risk factor for long-term cognitive impairment after ARDS.…”
Section: Perspectivesmentioning
confidence: 99%